DASAR-DASAR HUKUM PERJANJIAN SYARIAH DAN PENERAPANNYA DALAM TRANSAKSI SYARIAH - Dahrul Muftadin (Al-'Adl, 2018)
The existing Sharia Financial Institution (LKS) is the result of the scholarsto bring people closer to the sharia system. And now a days LKS is an alternativefor many people who want to have a transaction within the framework of sharia.The development of existing LKS is quite significant. Although in terms ofpercentage is still small when it is compared with the conventional financial institutions. Nevertheless, the spirit for alms should always be well appreciated forsharia financial institutions to grow.In order for sharia financial institutions to develop properly in accordancewith the existing signs in Islamic law, the Islamic financial institutions must meetthe criteria and conditions which is still valid.The principles or basics that have been determined that will later make allthe forms of transaction done in terms of finances can run in accordance with the existing Shari'a. So as to create a balance that can provide benefits for the partieswho make sharia transactions.